Silica-based transparent barrier layers for solar cells application. (2016) - Startek, Kamila; Kargol, Marta; Granek, Filip
Abstract: Flexible films with high barrier properties against water and oxygen are currently in the focus for applications in an increasing number of technical fields, e.g. electronic and optical devices. In this research work, high performance functional coatings, based on hybrid organic/inorganic materials, are being developed to combine the polymer flexibility and ease of processing with the rigidity and thermal stability of inorganic materials. The main goal was to obtain low-cost and low-temperature barrier layer for flexible solar cells with high transparency and hydrophobic properties. Surface morphology and surface performance together with hydrophobic and optical properties were examined and compared for various samples. Moreover, some preliminary permeability tests were carried out for selected samples to indicate for some improvement in terms of barrier quality.